Fibrinolytic Serine Proteases, Therapeutic Serpins and Inflammation: Fire Dancers and Firestorms - Yaron, Jordan R.; Zhang, Liqiang; Guo, Qiuyun; Haydel, Shelley E.; Lucas, Alexandra R. (Frontiers in Cardiovascular Medicine, 2021)
The making and breaking of clots orchestrated by the thrombotic and thrombolytic serine protease cascades is a critical determinant of morbidity and mortality during infection and with vascular or tissue injury. Both the clot forming (thrombotic) and the clot dissolving (thrombolytic or fibrinolytic) cascades are composed of a highly sensitive and complex relationship of sequentially activated serine proteases and their regulatory inhibitors in the circulating blood. The proteases and inhibitors interact continuously throughout all branches of the cardiovascular system in the human body, representing one of the most abundant groups of proteins in the blood. There is an intricate interaction of the coagulation cascades with endothelial cell surface receptors lining the vascular tree, circulating immune cells, platelets and connective tissue encasing the arterial layers. Beyond their role in control of bleeding and clotting, the thrombotic and thrombolytic cascades initiate immune cell responses, representing a front line, "off-the-shelf" system for inducing inflammatory responses. These hemostatic pathways are one of the first response systems after injury; the fibrinolytic cascade being one of the earliest to evolve in primordial immune responses. The other ancient component of these cascades are the serine protease inhibitors, termed serpins. Serpins are metastable suicide inhibitors with ubiquitous roles in coagulation and fibrinolysis as well as multiple central regulatory pathways throughout the body. Serpins are now known to also modulate the immune response, either via control of thrombotic and thrombolytic cascades or via direct effects on cellular phenotypes, among many other functions. Here we review the co-evolution of the thrombolytic cascade and the immune response in disease and in treatment. We will focus on the relevance of these recent advances in the context of the ongoing COVID-19 pandemic. SARS-CoV-2 is a "respiratory" coronavirus now discovered to have extensive cardiovascular pathogenesis, with microthrombi throughout the vascular tree, resulting in severe and potentially fatal coagulopathies.